Testability of electronic circuits - Weyerer, Manfred; Goldemund, Gerald (German : Carl hanser Verlag, 1992)
Recognizing the increasing complexity of electronic components, this comprehensive book presents a complete overview of the technology and economics of building testability into the design of electronic circuits. Offering background techniques and practical applications for the design of testability in digital, analog and hybrid circuits, the text exposes the problems in testing electronic circuits during manufacturing and maintenance; offers practical examples and current techniques for circuit design that includes testability; describes both hardware and software technologies used in automatic testing and places heavy emphasis on computer aided testing technology and its relation to computer aided design.
Keywords: DIGITAL ELECTRONICS -- TESTING